Orientation of Da'wah; Reinterpreting the Goals and Essence of Islamic Da'wah - Uliyah, Taqwatul (West Science Interdisciplinary Studies, 2025)
In recent times, Indonesian society has been filled with the phenomenon of loud preachers who continue to call for hate speech, slander, and hoaxes in the name of Islam. Not only non-Muslims, but also Muslims are afraid to see Islam. The theory of Islam that should have "saved" suddenly appeared in a way that was full of hatred, resulting in a campaign that "harms" humans and their environment. Much Islamic material is reduced to just preaching teachings, jihad, which is a war against "enemies of Islam." This situation must be explained by re-elevating the eternal teaching of Islam, "salvation." This article complements the discussion of the contemporary preaching phenomenon and aims to strengthen the idea that carrying out "social media jihad" is important to counter radical preaching today. The thick description method is used to read the phenomenon of preaching on social media that has been rampant lately, especially those containing elements of violence and radicalism. This method shows the strengthening of millennial conservatism in social media and their real movements. It is also hoped that policy makers, both from the government and moderate Islamic groups, have the ability to implement laws and have the courage to seriously fight radical preaching.